2014
DOI: 10.1016/j.redox.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of oxidative stress by thioredoxin reductase: Cysteine versus selenocysteine

Abstract: Thioredoxin reductase (TR) catalyzes the reduction of thioredoxin (TRX), which in turn reduces mammalian typical 2-Cys peroxiredoxins (PRXs 1–4), thiol peroxidases implicated in redox homeostasis and cell signaling. Typical 2-Cys PRXs are inactivated by hyperoxidation of the peroxidatic cysteine to cysteine-sulfinic acid, and regenerated in a two-step process involving retro-reduction by sulfiredoxin (SRX) and reduction by TRX. Here transient exposure to menadione and glucose oxidase was used to examine the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Interestingly, under normal conditions disulfide-bonded PRX3 dimers appear to be relatively long lived. After cessation of acute oxidative stress, disulfide-bonded PRX3 dimers persist for several hours in mouse lung epithelial cells, and their rate of reduction is dictated by the activity of TR2 [ 59 ]. Thus, the presumed catalytic intermediate targeted by TS is both present and persistent in MM tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, under normal conditions disulfide-bonded PRX3 dimers appear to be relatively long lived. After cessation of acute oxidative stress, disulfide-bonded PRX3 dimers persist for several hours in mouse lung epithelial cells, and their rate of reduction is dictated by the activity of TR2 [ 59 ]. Thus, the presumed catalytic intermediate targeted by TS is both present and persistent in MM tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, gold was bound at three different sites, not directly involving the C‐terminal SeC residue. The TrxRs are very insensitive or slow responders to the direct or rapid effects of cytotoxic cellular levels of H 2 O 2, based upon the insensitivity of their SeC to inactivation by this peroxide, but rather, the TrxR/Trx system preferentially acts on the more rapid acting Prxs, suggesting that TrxR functions at the top of the redox pyramid (Figure A and B) by regulating the oxidation state of the Prxs and other protein factors to dictate a hierarchy of phenotypic responses to oxidative stress …”
Section: Repurposing Drugs As Potent Pro‐oxidative Anticancer Agentsmentioning
confidence: 99%
“…The TrxRs are very insensitive or slow responders to the direct or rapid effects of cytotoxic cellular levels of H 2 O 2, based upon the insensitivity of their SeC to inactivation by this peroxide, but rather, the TrxR/Trx system preferentially acts on the more rapid acting Prxs, suggesting that TrxR functions at the top of the redox pyramid ( Figure 5A and 5B) by regulating the oxidation state of the Prxs and other protein factors to dictate a hierarchy of phenotypic responses to oxidative stress. 156,167 TrxR2-deficient embryonic fibroblasts are highly sensitive to endogenous ROS when GSH synthesis is inhibited and TrxR2 knockout is embryonic lethal, establishing that TrxR2 plays an essential role in cell survival. 119 Moreover, studies of isolated heart mitochondria 168 respiring on glutamate/malate showed a 10-fold decrease in the ratio of oxidized to reduced TrxR2.…”
mentioning
confidence: 99%
“…Hepatocytes were transfected with TXNRD1-targeting siRNA (sense, 5′-CCAUAGAGGGCGAAUUUAAUU-3′; antisense, 5′-UUAAAUUCGCCCUCUAUGGUU-3′) [22] using the Lipofectamine 2000 reagent (Invitrogen) according to the manufacturer's instructions. A control siRNA (sense, 5′-ACGUGACACGUUCGGAGAAUU-3′; antisense, 5′-UUCUCCGAACGUGUCACGUUU-3′) was also used.…”
Section: Sirna-mediated Knockdown Of Txnrd1mentioning
confidence: 99%